Home Environmental Contamination Is Associated with Community-associated Methicillin-resistant Staphylococcus aureus Re-colonization in Treated Patients. (4th October 2017) - Davis, Meghan; Morris, Daniel; Cluzet, Valerie; Bilker, Warren; Tolomeo, Pam; Julian, Kathleen G; Baron, Patrick; Brazil, Amy; Ferguson, Jacqueline; Iverson, Sally Ann; Shahbazian, Jonathan; Ludwig, Shanna; et al.
Abstract: Background: Strategies to interrupt household transmission of community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) that target human colonization show mixed results. Our aim was to determine whether home environmental contamination and pet carriage with MRSA were associated with re-colonization or persistent colonization of index patients diagnosed with CA-MRSA skin or soft-tissue infection (SSTI). Methods: Index patients from a randomized controlled trial (NCT00966446) that tested household-wide decolonization of people were eligible to participate in this substudy. Before randomization, eight environmental sites and all pets were sampled in the home. Patients were treated by their physician for the initial SSTI between diagnosis (visit 0) and the home visit (visit 1). They provided swabs every 2 weeks for 3 months (7 visits). After broth-enrichment culture, MRSA isolates were PCR-confirmed and spa -typed. Results: Of 88 index patients recruited from the main trial, 64 (73%) provided swabs for ≥3 visits and were included in this analysis. At visit 1, 41 (64%) households were MRSA contaminated and 6 (9%) had MRSA-positive pet(s). All MRSA-positive pets lived in homes with MRSA environmental contamination. After visit 1, 42 (66%) index patients and their household members were block-randomized to nasal mupirocin and chlorhexidine body wash decolonization. Thirty-seven (58%) index patients had two consecutive negative swabs (de-colonized); 13 (35%) of these later were MRSA-positive (re-colonized). Patients with home contamination had higher rates of re-colonization than those without (Cox proportional hazard ratio 6.0 [95% CI: 1.2, 30.6], P < 0.03). Persistent colonization (all or all but one swab positive) was identified in 6 (9%) of index patients and was associated with identification of matching spa -types in environmental and subsequent human MRSA isolates ( P < 0.05). Conclusion: In patients with MRSA SSTI, MRSA-contaminated homes, and potentially MRSA-positive pets, are associated with re-colonization and persistent colonization. Future studies are needed to determine whether environmental decontamination can improve the success of household decolonization interventions. Disclosures: All authors: No reported disclosures.